Holiday colonies in the first half of the twentieth century: a comparison between Italian and French experiences - Comerio, Luca Andrea Alessandro (Rivista di Storia dell’Educazione, 2018)
Description of an ongoing research on holiday colonies, an important example of non-school education, present in many different national contexts. The comparison of the two Italian and French cases allows us to verify the differences and similarities of experiences in which pedagogical, political and institutional dimensions are intertwined. For the Italian case the essay also uses photographic archive sources.